Response to "Rating Teachers Cheaper, Faster, and Better: Not So Fast": It's About Evidence. (September 2015) - Gargani, John; Strong, Michael
In Gargani and Strong (2014), we describe The Rapid Assessment of Teacher Effectiveness (RATE), a new teacher evaluation instrument. Our account of the validation research associated with RATE inspired a review by Good and Lavigne (2015). Here, we reply to the main points of their review. We elaborate on the validity, reliability, theoretical foundation, purposes, and value of RATE; answer Good and Lavigne's criticisms; and discuss the role evidence plays in research, especially when it challenges strongly held theories.